CHOROIDAL THICKENING AND PACHYCHOROID IN CUSHING SYNDROME: Correlation With Endogenous Cortisol Level. Issue 2 (February 2019) - Wang, Erqian; Chen, Shi; Yang, Hongbo; Yang, Jingyuan; Li, Yanlong; Chen, Youxin
Abstract : Purpose: To investigate subfoveal choroidal thickness and pachychoroid and their correlation with hormone level in patients with endogenous Cushing syndrome (CS). Methods: We enrolled a consecutive series of patients with CS and healthy controls. All participants had swept-source optical coherence tomography. All patients with CS had hormone test including morning plasma-free cortisol, 24-hour urine-free cortisol (24UFC), and plasma adrenocorticotropic hormone. We compared subfoveal choroidal thickness and pachychoroid changes between two groups. We performed univariate and multivariate analysis to study correlation between hormone level and choroid thickness as well as pachychoroid in patients with CS. Results: Compared with control group, Cushing group had significantly greater subfoveal choroidal thickness (371.6 ± 114.9 and 320.0 ± 74.0, P = 0.002) and higher proportion of eyes with pachychoroid (53.1 and 14.3%, P < 0.001). Subfoveal choroidal thickness was significantly correlated with 24UFC ( P = 0.007) but not with plasma-free cortisol ( P = 0.48) or adrenocorticotropic hormone ( P = 0.56). Pachychoroid was significantly correlated with 24UFC ( P = 0.03) but not with plasma-free cortisol ( P = 0.24) or adrenocorticotropic hormone ( P = 0.32). Conclusion: There was a positive correlation between elevated 24UFC and choroid thickening as well as pachychoroid, indicating the importance of normal endogenous cortisol level in maintaining the human choroid vasculature. Abstract : Patients with endogenous Cushing syndrome tended to have increased subfoveal choroidal thickness and pachychoroid, which were significantly correlated with elevated 24-hour urine cortisol.